Do teaching staff in primary schools perceive any impacts of school-based counselling on school engagement?. Issue 2 (4th March 2022) - Raynham, Helen; Jinks, Gordon
ABSTRACT: Teaching assistants and teachers ( N  = 186) in Cambridgeshire primary schools in the UK were invited to participate in a survey to explore the perceived impact of school-based counselling (SBC) on pupils' cognitive, social, and emotional engagement. Participants were also asked which of these factors they believed were most important to a child's educational progress. T -tests and one-way ANOVAs were conducted to explore the findings. Perceived effects of SBC were greatest on pupils' social engagement ( M  = 18.05, SD  = 4.17), followed by emotional engagement ( M  = 16.71, SD  = 5.24) and cognitive engagement ( M  = 15.08, SD  = 3.96). Emotional engagement was reported as the most important factor in a child's educational progress χ 2 (2, n  = 169)  = 77.834, p  < .0001.